2017
DOI: 10.1038/ejcn.2017.10
|View full text |Cite
|
Sign up to set email alerts
|

Low muscle mass at initiation of anti-TNF therapy for inflammatory bowel disease is associated with early treatment failure: a retrospective analysis

Abstract: Identifying low muscle mass at anti-TNF induction as a risk factor for treatment failure may contribute to a more tailored approach to IBD therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 39 publications
2
35
0
Order By: Relevance
“…These findings are similar to adult studies where sarcopenia prevalence in the pre‐LTx and post‐LTx periods has been reported to range 30%–70% . Sarcopenia prevalence was highest in female children <10 years, a finding that has been reported in other studies where significant lean body mass deficits have been reported in younger female children with newly diagnosed and longer term Crohn's disease . Although linear growth and weight gain were within normal reference ranges in the majority of children, sarcopenia was associated with reduced linear growth and weight gain when compared with children without sarcopenia.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These findings are similar to adult studies where sarcopenia prevalence in the pre‐LTx and post‐LTx periods has been reported to range 30%–70% . Sarcopenia prevalence was highest in female children <10 years, a finding that has been reported in other studies where significant lean body mass deficits have been reported in younger female children with newly diagnosed and longer term Crohn's disease . Although linear growth and weight gain were within normal reference ranges in the majority of children, sarcopenia was associated with reduced linear growth and weight gain when compared with children without sarcopenia.…”
Section: Discussionsupporting
confidence: 88%
“…11,12,[30][31][32][33] Sarcopenia prevalence was highest in female children <10 years, a finding that has been reported in other studies where significant lean body mass deficits have been reported in younger female children with newly diagnosed and longer term Crohn's disease. 18,34,35 Although linear growth and weight gain were within normal reference ranges in the majority of children, sarcopenia was associated with reduced linear growth and weight gain when compared with children without sarcopenia. This was particularly evident in the first year post-LTx where catch-up linear growth was not observed in the children with sarcopenia.…”
Section: Discussionmentioning
confidence: 93%
“…FC, as a measure of luminal inflammation in IBD, was negatively associated with ASMI, which is consistent with the known catabolic effects of chronic inflammation [ 18 , 20 , 47 ]. Lean mass is important in patients with IBD, and has been shown to have a bearing on response to therapy, surgical outcomes, and quality of life [ 15 , 18 , 20 , 48 , 49 ]. Grip strength proved to be a simple anthropometric test that was independently and positively associated with ASMI, while also negatively associated with FMI.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research indicates that an increased rate of major postoperative complications is correlated with IBD-induced myopenia, including mortality and morbidity (14,15). In addition, low LM at the initiation of anti-TNF treatment is also indicative of higher nonresponse rates (16). Although these relations may be heightened due to the severity of disease at time of surgery or initiation of biologics, the impact of LM on both current and future disease outcomes is critical.…”
Section: Lean Body Mass In Pediatric Inflammatory Bowel Diseasementioning
confidence: 99%